2014
DOI: 10.1128/jcm.02177-13
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Changes in Clostridium difficile Testing Practices on Stool Rejection Policies and C. difficile Positivity Rates across Multiple Laboratories in the United States

Abstract: We describe the adoption of nucleic acid amplification tests (NAAT) for Clostridium difficile diagnosis and their impact on stool rejection policies and C. difficile positivity rates. Of the laboratories with complete surveys, 51 (43%) reported using NAAT in 2011. Laboratories using NAAT had stricter rejection policies and increased positivity rates. Clostridium difficile infection (CDI) continues to be an important public health problem due to its high incidence, morbidity, and medical care costs (1, 2). Rapi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 15 publications
2
31
0
Order By: Relevance
“…Compared to current practices at our institution and other U.S. hospitals where nearly all patients with positive C. difficile PCR results are treated for CDI (16,17), reporting C T toxin result in addition to PCR result has the potential to reduce anti-C. difficile therapy by 45.8% based on results of this study (143 of 312 PCR-positive samples were C T toxin negative), if only toxin-positive patients are treated. This approach has the potential to have far-reaching impact as stand-alone C. difficile NAAT has been widely adopted for CDI diagnosis in the United States (18). Further studies are needed to implement C T toxin reporting under routine clinical practice and measure its impact on provider behavior, patient outcomes, and antibiotic stewardship.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to current practices at our institution and other U.S. hospitals where nearly all patients with positive C. difficile PCR results are treated for CDI (16,17), reporting C T toxin result in addition to PCR result has the potential to reduce anti-C. difficile therapy by 45.8% based on results of this study (143 of 312 PCR-positive samples were C T toxin negative), if only toxin-positive patients are treated. This approach has the potential to have far-reaching impact as stand-alone C. difficile NAAT has been widely adopted for CDI diagnosis in the United States (18). Further studies are needed to implement C T toxin reporting under routine clinical practice and measure its impact on provider behavior, patient outcomes, and antibiotic stewardship.…”
Section: Discussionmentioning
confidence: 99%
“…Changes to sampling and testing policy and methodology clearly affect CDI positivity rates. 22,23 In the UK there has been a national campaign to reduce the incidence of CDI and to standardise laboratory diagnosis. 24 The proportion of UK PHs using methodology consistent with the SRM was the highest of all countries, in line with national guidelines;…”
Section: Discussionmentioning
confidence: 99%
“…The use and implications of differential CDI case detection methods have been described in recent studies [6,15,90,91]. In Europe, it was shown that testing policies varied widely, a factor that contributed to a large number of CDI cases being missed on a daily basis.…”
Section: Resultsmentioning
confidence: 99%
“…A notable exception was the UK, where both under– and misdiagnosis is uncommon, as national guidelines have been introduced to standardise laboratory diagnosis including confirmatory procedures [15,43]. In the US, 43% of 120 laboratories surveyed used molecular assays as first– or second–line for diagnosis of CDI, similarly to the percentage using enzyme immunoassay tests alone (42%) [91]. In this survey, use of molecular tests was more likely to be accompanied by higher rejection rates for unnecessary testing (ie, formed stools, test for cure, or duplicates within 7 days).…”
Section: Resultsmentioning
confidence: 99%